World Bank Support to Reducing Child Undernutrition : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2021)
Insufficient intake or absorption of nutrients results in undernutrition in children and negatively affects their health, physical growth, and cognitive development. These and other nutrition outcomes are affected by immediate determinants that include caregiving practices, dietary intake or diversity, and the health status of the mother and child. These immediate determinants are all difficult to realize when communities lack adequate underlying determinants of nutrition, such as access to nutrient-rich food, caregiving resources, health care, and water, sanitation, and hygiene (WASH) services. Successfully addressing both the immediate and underlying determinants of nutrition requires changing behaviors related to feeding, caregiving, health, and WASH practices throughout the life cycle of the mother and child and social norms related to early marriage, early pregnancy, birth spacing, and women’s empowerment. This evaluation assesses the contributions of the World Bank to improving nutrition determinants and outcomes for children through its interventions during fiscal years (FY) 2008–19. The evaluation uses a variety of evidence at the global, country, and portfolio levels. Its findings are intended to inform the design of future nutrition support.